The Ascidia Ciona robusta Provides Novel Insights on the Evolution of the AP-1 Transcriptional Complex - Marotta, Pina; Salatiello, Federica; Ambrosino, Luca; Berruto, Federica; Chiusano, Maria Luisa; Locascio, Annamaria (Frontiers in Cell and Developmental Biology, 2021)
The AP-1 transcriptional complex is historically defined as an early response group of transcription factors, formed by dimeric complexes of the Jun, Fos, Atf, and Maf bZIP proteins that control cell proliferation and differentiation by regulating gene expression. It has been greatly investigated in many model organisms across metazoan evolution. Nevertheless, its complexity and variability of action made its multiple functions difficult to be defined. Here we place the foundations for understanding the complexity of AP-1 transcriptional members in tunicates. We investigated the gene members of this family in the ascidian Ciona robusta and identified single copies of Jun, Fos, Atf3, Atf2/7, and Maf bZIP related factors that could have a role in the formation of the AP-1 complex. We highlight that mesenchyme is a common cellular population where all these factors are expressed during embryonic development, and that, moreover, Fos shows a wider pattern of expression including also notochord and neural cells. By ectopic expression in transgenic embryos of Jun and Fos genes alone or in combination, we investigated the phenotypic alterations induced by these factors and highlighted a degree of functional conservation of the AP-1 complex between Ciona and vertebrates. The lack of gene redundancy and the first evidences of conserved functions in the control of cell movements and structural organization exerted by these factors, open the way for using Ciona as helpful model system to uncover the multiple potentialities of this highly complex family of bZIP transcription factors.